Application Research of Extracting Slope DEM Data by GB-SAR. Issue 6 (April 2019) - Zhou, Xiao; Li, Zhenming; Li, Changjun; Xing, Cheng
Abstract: Ground-based Synthetic Aperture Radar (SAR) adopts the step-frequency continuous wave technology, synthetic aperture radar technology and interferometric measurement technology, to achieve all-weather, non-contact, high-accuracy deformation monitoring on the target. The slope DEM data may be extracted by increasing the radar vertical baseline and constructing the geometric model between the target slope and the radar. In this paper, the geometric model of the radar with vertical baseline and the target is analyzed firstly; the factors affecting the accuracy of target DEM data are summarized secondly; and the technology is verified through the use of the measured slope data finally. The results show that GB-SAR can extract the slope DEM data quickly, and the generated DEM data may be used to assist the recognition of the target radar image.